Optimasi konseling behavioral melalui teknik self management untuk mengatasi perilaku membolos - Dewi, Anisha Fitri; Dantes, Nyoman; Lestari, Luh Putu Sri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study aims to determine the effect of a behavioral approach with self-management techniques to minimize truancy behavior in class XI students of SMAN 4 Singaraja. The design in this study used